Application of the phenomenology of Amedeo Giorgi as methodological support - Martínez Ávila, Brenda (2021)
The phenomenological method allows us to understand the meaning of people's lived experiences about a particular phenomenon to be investigated, its interest is to return to the very essence of things, that is, to revive the experience that occurred in order to build or rebuild knowledge based on it, but how is Amedeo Giorgi's phenomenology applied as methodological support?  Therefore, the objective of this essay is to explain the application of Amedeo Giorgi's phenomenology as a methodological support for the study of daily life experiences in adolescents, children of parents with dependent alcohol consumption. It is concluded that by looking for the essences and using the invariant and invariable of the particular phenomenon of study, the researcher can discover the concrete experience of the participants and reflect on the different possibilities of meanings of their experiences, that is, he tries to reach the essential. The purpose of Giorgi's method is to discover and articulate the meanings that the participant experienced through the phenomenon under investigation. Finally, applying the phenomenology of Amedeo Giorgi as methodological support in the study of the experiences of daily life allows us to understand the singular perspective from which adolescents see the real world in which they live, which is contextualized in an environment of dependent consumption of alcohol of their parents where the typical typifications of the daily life of the actors will clarify the interpretation that they give to their motives and actions.   Keywords: Phenomenology, methodology, alcoholism, parents, adolescence.